2010
DOI: 10.1111/j.1365-2036.2010.04324.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: the effects of a probiotic mixture on non‐steroidal anti‐inflammatory drug enteropathy – a randomized, double‐blind, cross‐over, placebo‐controlled study

Abstract: SUMMARY BackgroundNon-steroidal anti-inflammatory drugs (NSAIDs) can cause serious gastrointestinal side effects. Faecal calprotectin assay represents a simple and practical method for diagnosis of NSAID enteropathy. Intestinal micro-organisms are necessary for the development of NSAID-induced small bowel lesions and hence it has been suggested that probiotics could protect against NSAID enteropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 29 publications
2
54
1
6
Order By: Relevance
“…Administration of Lactobacillus casei (L. casei) has been shown to prevent the development of experimental colitis [18]. Furthermore, recent observations also support the role of probiotics in the treatment of NSAID-induced small bowel mucosal inflammation [19,20]. L. casei has been demonstrated to exhibit a preventive effect on indomethacininduced small bowel injury in an animal experiment [19].…”
Section: Introductionmentioning
confidence: 93%
“…Administration of Lactobacillus casei (L. casei) has been shown to prevent the development of experimental colitis [18]. Furthermore, recent observations also support the role of probiotics in the treatment of NSAID-induced small bowel mucosal inflammation [19,20]. L. casei has been demonstrated to exhibit a preventive effect on indomethacininduced small bowel injury in an animal experiment [19].…”
Section: Introductionmentioning
confidence: 93%
“…Only two clinical trials of a probiotic for NSAIDenteropathy have been reported to date. Montalto et al [115] performed a randomized, double-bind, placebo-controlled trial of VSL#3, a probiotic formulation consisting of 8 different live bacteria. Volunteers received indomethacin daily for 4 d, and fecal calprotectin levels were the endpoint.…”
Section: Nsaid-enteropathymentioning
confidence: 99%
“…Кальпротектин измеряли за день до начала приема пробиотика или плацебо и каждый день с 15-го по 21-й день ис-следования. Прием пробиотика до и во время терапии индоме-тацином значительно снизил уровень анализируемого показа-теля по отношению к плацебо [58]. В проспективном исследова-нии 35 пациентов, которые получали на протяжении более 3 мес (100 мг/сут) кишечно-растворимого АСК в сочетании с омепра-золом (20 мг/сут), рандомизировали в группу приема и отсут-ствие приема препарата, содержащего Lactobacillus сasei.…”
Section: терапевтический архив 12 2014unclassified